Smart Energy Management for Smart Grids - Longe, Omowunmi Mary (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a contribution from the authors, to share solutions for a better and sustainable power grid. Renewable energy, smart grid security and smart energy management are the main topics discussed in this book.